Hubungan Dukungan Keluarga Terhadap Kepatuhan Pola Makan Sehat Pada Lansia Penderita Hipertensi di Puskesmas Sungai Bilu Banjarmasin - Muhammad Hafiz Nugraha; Roly Marwan Mathuridy; Didy Ariady (CV. ITTC INDONESIA, 2025)
Hypertension is one of the chronic diseases commonly experienced by the elderly and can lead to serious complications if not properly managed. One of the strategies for managing hypertension is adherence to a healthy diet. However, in practice, many elderly individuals remain non-compliant, which is suspected to be influenced by a lack of family support. The family plays an important role in shaping healthy habits among the elderly, including dietary and lifestyle choices. This study aims to determine the relationship between family support and adherence to a healthy diet among elderly patients with hypertension at Sungai Bilu Public Health Center, Banjarmasin. This research is a quantitative study with a cross-sectional design. The sample consisted of 50 elderly individuals with hypertension, selected using accidental sampling techniques. The instrument used was a questionnaire that had been tested for validity and reliability. Data were analyzed using the Chi-Square statistical test. The analysis results showed a very strong and significant relationship between family support and adherence to a healthy diet among the elderly, with a Chi-Square coefficient value of 28.448 and a significance value of p < 0.000.